2012
DOI: 10.1590/s1516-35982012000800021
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion problems of broiler chickens and its relationship with the gait score

Abstract: -The objective of this study was to evaluate the correlation between the ability to walk (gait score), incidence of femoral degeneration, tibial dyschondroplasia, valgus and varus deformity and leg symmetry of broiler chickens. Male chickens of the Cobb strain from a commercial poultry farm were utilized in this experiment. Fifty 35 and 42-day-old birds were evaluated according to the gait score and valgus or varus incidence. To assess the bilateral symmetry and the lesion score for femoral degeneration and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 9 publications
2
20
1
Order By: Relevance
“…A total of 19.5% of broilers had VAL, and 7.6% presented VAR. The total percentage of angular deformities was lower than those found in the current literature (Fernandes et al, 2012). Almeida Paz et al (2010) indicated that nearly 32% of commercial broilers had angular leg deformities; however, no difference was found between sex and genetic strains.…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…A total of 19.5% of broilers had VAL, and 7.6% presented VAR. The total percentage of angular deformities was lower than those found in the current literature (Fernandes et al, 2012). Almeida Paz et al (2010) indicated that nearly 32% of commercial broilers had angular leg deformities; however, no difference was found between sex and genetic strains.…”
Section: Resultscontrasting
confidence: 52%
“…Although visually there is a high percentage of broilers commonly walking on commercial farms, this might not mean that there are only sound birds in the flock (Fernandes et al, 2012). The difference found between the commercial strains and the indigenous chicken might be assigned to various factors, the most critical of which are the weight distribution and the way broilers gain weight during the grow-out period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the limited mobility of the chickens is more related to problems of joint deviations (FERNANDES et al, 2010). The same authors found a significant difference for articulation deviations between right and left legs and the different degrees of gait score with the largest deviation of articulation related to gait score 2 (a bird having walking trouble), indicating that this deformity can be related to gait score and age.…”
Section: Resultsmentioning
confidence: 93%
“…When varus is present in one leg (negative angle), the bird tries to compensate this deviation by placing most of the body weight on the other leg, overloading the limb. Fernandes et al (2012) analyzed the correlation between gait score and valgus deformity and found that the displacement of the hock joint on its axis was a source of valgus deformity of both right and left legs. Therefore, leg disorders are not always related to femoral degeneration or tibial dyschondroplasia.…”
Section: Resultsmentioning
confidence: 99%